New insights on black rot of crucifers : disclosing novel virulence genes by in vivo host/pathogen transcriptomics and functional genetics - Cruz, Joana Costa Cardoso da (2017)
Tese de doutoramento, Biologia (Microbiologia), Universidade de Lisboa, Faculdade de Ciências, 2018